A red phosphorus-graphite composite as anode material for potassium-ion batteries. (September 2021) - Capone, Isaac; Aspinall, Jack; Lee, Hyeon Jeong; Xiao, Albert W.; Ihli, Johannes; Pasta, Mauro
Abstract: Red phosphorus (RP) is a promising anode material for potassium-ion batteries because of its theoretical capacity of 865 mAh/g delivered at an average potential of 0.5 V vs. K + /K. However, its alloy reaction to form KP entails a volume expansion of 162% resulting in severe stresses that lead to SEI and electrode fracture, loss of electric contact, and ultimately reduced cycle life. Moreover, its low electronic conductivity (10 −14 S/cm) limits rate capability. Here, we report an RP-graphite composite prepared by a two-step ball-milling procedure to control particle size and optimize carbon coating. Raman operando on graphite in the composite suggests that the carbon coating reversibly expands and contracts due to the volume expansion of RP particles. Electrodes prepared with the composite achieve high capacity (723 mAh/gP ) at C/20 and retaining 75% at 5C. It also shows very good cycling stability, retaining more than 96% of the capacity after 100 cycles at 1C. Graphical abstract: Image 1 Highlights: Red Phosphorous (RP)-graphite composite anode for K-ion batteries. Two step ball milling synthesis procedure to control particle size and carbon coat the RP particles. Operando Raman suggests that the carbon coating reversibly expands and contracts due to the volume expansion of RP particles. Electrodes prepared with the composites achieve a capacity of (723mAh g1 P ) at C/20 and retain 75% at 5C. 96% of the initial capacity is retained after 100 cycles at 1C.,